Blue Economy and sustainable tourism management in coastal zones: Learning from experiences - Marios Sotiriadis; Shiwei Shen (Asian Development Bank Institute (ADBI), 2020)
The sustainable management of coastal zones requires appropriate tools within the framework of the Blue Economy. This paper adopts a supply/coastal zone perspective to investigate key issues and aspects related to the implementation of coastal tourism initiatives. The main research question is: "What lessons could we take from practical experiences?" A related question is: "What are the critical factors for effective implementation?" The paper's aim is to suggest a framework of essential factors and guidelines for successful and effective implementation of related projects. The study's focus is on gaining insight and capitalizing on experience from Integrated Coastal Zone Management plans implemented in four countries.
Keywords: M0; O2; 330; sustainable tourism management; coastal zone; integrated framework; implementation; critical success factors; case study; Asia